Hubungan Penggunaan Komunikasi Efektif SBAR Terhadap Kualitas Pelaksanan Handover - Wijayanti Wijayanti; Triastuti Handayani; Luluk Purnomo (STIKes Ibnu Sina Ajibarang, 2023)
Hospitals as providers of health services for the wider community are required to provide health services with good quality health services. The quality of hospital services can be achieved one of them with SBAR communication, so that the information conveyed can be informative and well received which will improve the handover process so that patient safety can be realized. The purpose of this study was to determine the relationship between effective SBAR communication and the quality of handover implementation in the Inpatient Room of JIH Solo Hospital. The sampling technique used is total sampling. The number of respondents was 90 respondents divided into 72 nurses and 18 midwives who were given observation sheets using the SBAR communication method and observation sheets for the quality of handover implementation. Variable correlation assessment using the chi-square test. The results of the analysis of the relationship between variables are significant with a sig value of 0.000 (p=0.05). Then, the value of the correlation coefficient between variables is very strong, namely 0.979. The use of effective SBAR communication resulted in the majority of respondents namely 79 people or 85.7% being categorized as qualified. In its implementation, the majority of respondents with a total of 87 people (196.7%) were categorized as qualified.